Evaluation of clinico-epidemiological factors and outcome of COVID-19 disease in perinatal period - Dabhadkar, Suchita V.; Taralekar, Vaishali S.; A., Mahima R.; Barsode, Salil D.; Kale, Pooja S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It is well accepted that pregnant women are at increased risk of infections, morbidity from known respiratory viruses like H1N1, varicella, influenza. COVID-19, a virus from the same family poses a greater and influential risk to the health of our mothers and their babies. Raised concerns of pregnant women, being physiologically immunocompromised with associated comorbidities like hypertension, diabetes, heart disease, anemia is very challenging for the obstetrician to conquer. Methods: We tested 405 pregnant women for PCR SARS CoV-2 during the pandemic out of which 59 pregnant women turned out to be positive, and were included in the study analysis. These women had singleton live pregnancy beyond 37 weeks and opted for in patient management. Study participants did not have any known obstetric complications. Results: 81% of women were delivered by cesearean section, indication being premature rupture of membranes and anhydramnios in 45 % of women reflecting the infective etiology of the disease. 60% women were asymptomatic, yet positive for the disease. Community spread was seen in 75% of the women. No ICU admissions were recorded. Conclusions: The substantial impact on the vulnerable groups like pregnancy has necessitated need for further studies and research and to build more service models as frontline obstetric COVID health care workers.